2022
DOI: 10.1007/s10439-022-02930-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Methods Using Spectralis OCT for Diagnosis and Disability Progression Prognosis in Multiple Sclerosis

Abstract: Machine learning approaches in diagnosis and prognosis of multiple sclerosis (MS) were analysed using retinal nerve fiber layer (RNFL) thickness, measured by optical coherence tomography (OCT). A cross-sectional study (72 MS patients and 30 healthy controls) was used for diagnosis. These 72 MS patients were involved in a 10-year longitudinal follow-up study for prognostic purposes. Structural measurements of RNFL thickness were performed using different Spectralis OCT protocols: fast macular thickness protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
3
28
0
Order By: Relevance
“…Likewise, Montolío et al [ 64 ] used OCT to measure patients’ RNFL thinness for MS diagnosis and prognosis using ML techniques. The study included 72 MS patients and 30 healthy controls, and the classifiers used in this study included SVM, Multiple Linear Regression (MLR), KNN, DT, NB, ensemble classifier (EC), and long short-term memory (LSTM-RNN).…”
Section: Related Studiesmentioning
confidence: 99%
“…Likewise, Montolío et al [ 64 ] used OCT to measure patients’ RNFL thinness for MS diagnosis and prognosis using ML techniques. The study included 72 MS patients and 30 healthy controls, and the classifiers used in this study included SVM, Multiple Linear Regression (MLR), KNN, DT, NB, ensemble classifier (EC), and long short-term memory (LSTM-RNN).…”
Section: Related Studiesmentioning
confidence: 99%
“…Previous studies have shown that RNFL thickness decreases over time in MS patients, with a gradually increasing trend. Previous studies have demonstrated that RNFL thickness is correlated with visual impairment, axon loss, brain atrophy, cognitive and physical disorders, and MRI abnormalities (14).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, researchers developed a system based on a convolutional neural network that can classify the disease according to the thickness of the OCT scans, thus assisting in the early diagnosis of the disorder [ 40 ]. Machine learning has also been successfully used to predict disability progression in pwMS by analysing RNFL thickness [ 41 ].…”
Section: Optical Coherence Tomography In Multiple Sclerosismentioning
confidence: 99%